A fast approximate implementation of the work function algorithm for solving the -server problem - Rudec, Tomislav; Manger, Robert (Central European journal of operations research, 2015)
In this paper we propose an approximate implementation of the work function algorithm (WFA) for solving the [Formula omitted]-server problem. Our implementation is based on network flow techniques, a novel network model, and flow cost reduction. Also, it is provided with a parameter that enables tradeoff between accuracy and speed. In the paper we present experiments, showing that the new implementation can mimic perfectly the original WFA and still run at least an order of magnitude faster than any known exact implementation.